An adaptable stage perfusion incubator for the controlled cultivation of C2C12 myoblasts. Issue 1 (4th November 2014) - Kurth, Felix; Franco-Obregón, Alfredo; Bärtschi, Christoph A.; Dittrich, Petra. S.
Abstract : Here we present a stage perfusion incubation system that allows for the cultivation of mammalian cells within PDMS microfluidic devices for long-term microscopic examination and analysis. Abstract : Here we present a stage perfusion incubation system that allows for the cultivation of mammalian cells within PDMS microfluidic devices for long-term microscopic examination and analysis. The custom-built stage perfusion incubator is adaptable to any x – y microscope stage and is enabled for temperature, gas and humidity control as well as equipped with chip and tubing holder. The applied double-layered microfluidic chip allows the predetermined positioning and concentration of cells while the gas permeable PDMS material facilitates pH control via CO2 levels throughout the chip. We demonstrate the functionality of this system by culturing C2 C12 murine myoblasts in buffer free medium within its confines for up to 26 hours. We moreover demonstrated the system's compatibility with various chip configurations, other cells lines (HEK-293 cells) and for longer-term culturing. The cost-efficient system are applicable for any type of PDMS-based cell culture system. Detailed technical drawings and specification to reproduce this perfusion incubation system is provided in the ESI.